On the Issue of Developing Creative Players in Team Sports: A Systematic Review and Critique From a Functional Perspective - Zahno, Stephan; Hossner, Ernst-Joachim (Frontiers in Psychology, 2020)
Driven by the practical goal of developing creative players, several approaches to training creativity have been proposed and underpinned by empirical studies in sport science. However, the scope of these studies encompasses various aspects, which have all been subsumed under the singular label of ‘creativity’. Therefore, this systematic review aims to disentangle the pursued lines of thought in order to facilitate the derivation of well-grounded recommendations for sports practice. To this end, 38 studies are presented and characterized in terms of their underlying conceptualizations and measures of creativity. In most studies, creativity is conceptualized as a player’s domain-specific divergent thinking (DT) ability, reflected by individual differences in the number, variety and originality of ideas he or she is able to generate in response to game situations. Empirical studies indicate that DT can be improved by practice. However, the critical assumption that an enhanced DT ability transfers to creative on-field actions has yet to be tested. On the basis of the reviewed literature, an alternative point of view is proposed. In line with a relational understanding of creativity and a functional approach to behavioural control, it is hypothesised that an enhanced repertoire of sensorimotor skills increases the probability for performing functional solutions that, within a specific social and cultural frame of reference, go beyond the expected and consequently appear creative to the observer. In the context of sports practice, the proposed conceptual re-orientation would then suggest, rather than seeking ways to improve players’ DT ability, to target sensorimotor skills that allow players to perform a variety of task-solutions and thus to act less predictably to the opponent – or in other words, more creative.